(untitled) (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
At the beginning of 2024, the Scandinavian Studies Programme at the Department of German and Scandinavian Studies at Sofia University St. Kliment Ohridski held the 3rd edition of the translation competition for literary prose and poetry for university and school students learning Scandinavian languages. The competition is dedicated to the memory of Prof. Vera Gancheva, a distinguished Scandinavianist, translator, teacher, publisher, and scholar. A total of 21 participants took part in the third edition, submitting 31 translations overall.